Doses e formas de aplicação de torta de filtro na produção de cana soca - Fravet, Paulo Roberto Fávero de (2007)
The great agricultural potential of Brazil is recognized internationally, occupying the position of producing greater of sugarcane of the world. The projected growth for production of sugarcane in the country will imply in the generation of great volume of the residues for the sugarcane industry, that if made use inadequately can cause great damages to the environment. On the other hand, these same residues can be used as source of nutrients, reducing the ambient contamination and the costs with fertilization. However, few studies exist on the amount and form of application of these residues in sugarcane-beats. The filter cake, one of the residues of the sugarcane industry, is presented as excellent organic product for the recovery of ground and with low fertility, as well as, for the supply of nutrients. The present research was carried through in ground of argillaceous texture, an area of commercial farming with system of conventional plantation and without irrigation, having for objective to evaluate the morphologic, technological, and productivity characteristics of the sugarcane (3rd raton) for different forms of application and dosage of filter cake. The experiment was installed using the experiment delineation of blocks design with ten (10) treatments and five (5) repetitions, in 5 factorial project X 2 + 1 that they correspond the 5 increasing dosage of filter cake (0, 10, 20, 40 and 80 t ha-1) combined the 2 ways of application (in the superficial line and the one between incorporated line) and a corresponding additional treatment to a mineral fertilization. The variety of the sugarcane used in the experiment was the SP 81-3250 with average cycle and demanding in fertility of the ground, being its plantation carried through in October of 2000. The experiment was after installed 3º cut of the canavial in September, 11 of 2003 and (4º cut of the canavial) in June, 28 of 2004. Were had been evaluated number of sptout for hectare to the 60 and 120 days after the installation of the experiment, average height and average diameter of sugarcane stalks (m), Brix of the broth (%), POL of the sugarcane (%), productivity of sugarcane for hectare and productivity of sucrose for hectare. The gotten results had shown that it had difference statistics for number of sptout for hectare in the interaction between application way and time of sampling. Significant difference was not observed, in none of the evaluated variable, for the different ways of application of the filter cake. The different dosage of applied filter cake had presented significant difference for height of sugarcane stalks, Brix, POL, TCH and TPH. From the results presented in this study, it was concluded that the filter cake application presented effect positive on sugarcane stalks, exactly in the dosage of 10 t ha-1, independently in the application way.